Distance Learning Courses: New Opportunities for the Development of University Education - Nataliia Wagner, Monica- (2021)
DL is a new means of implementing the learning process, which is based on the use of modern information and telecommunication technologies that allow studying at a distance without personal contact between the teacher and the student. DL is one of the main ways of computerization and automation of education and the use of the latest technologies in training and serves to increase the effectiveness of education as such. The organization of high-quality distance education will increase educational capacities and positively affect the intellectual potential of the state. This paper discusses the features of distance learning. The authors also describe the basic functional modules of modern distance learning management systems that contain access to educational materials and the means to ensure communication between participants in the distance learning process. According to the formulated modules, the authors perform a review and comparison of the availability and implementation of distance learning modules in such distance learning systems as Moodle, Claronline, ATutor, SharePointLMS, Live @ EDU, and eFront.